A dynamic 2000–540 Ma Earth history: From cratonic amalgamation to the age of supercontinent cycle - Li, Zheng-Xiang; Liu, Yebo; Ernst, Richard (Elsevier, 2023)
Establishing how tectonic plates have moved since deep time is essential for understanding how Earth's geodynamic system has evolved and operates, thus answering longstanding questions such as what “drives” plate tectonics. Such knowledge is a key component of Earth System science, and has implications for wide ranging fields from core-mantle-crust interaction and evolution, geotectonic phenomena such as mountain building and magmatic and basin histories, the episodic formation and preservation of Earth resources, to global sea-level changes, climatic evolution, atmospheric oxygenation, and even the evolution of life. In this paper, we take advantage of the rapidly improving database and knowledge about the Precambrian world, and the conceptual breakthroughs, both regarding the presence of a supercontinent cycle and possible dynamic coupling between the supercontinent cycle and mantle dynamics, in order to establish a full-plate global reconstruction from 540Ma back to 2000Ma. We utilise a variety of global geotectonic databases to constrain our reconstruction, and use palaeomagnetically recorded true polar wander events and global plume records to help evaluate competing geodynamic models and also provide new constraints on the absolute longitude of continents and supercontinents. After revising the configuration and life span of both supercontinents Nuna (1600–1300Ma) and Rodinia (900–720Ma), we present a 2000–540Ma animation, starting from the rapid assembly of large cratons and supercratons (or megacontinents) between 2000Ma and 1800Ma. This occurred after a billion years of dominance by small cratons, and kick-started the ensuing Nuna and Rodinia supercontinent cycles and the emergence of stable, hemisphere-scale (long-wavelength) degree-1/degree-2 mantle structures. We further use the geodynamicly-defined type-1 and type-2 inertia interchange true polar wander (IITPW) events, which likely occurred during Nuna (type-1) and Rodinia (type-2) times as shown by the palaeomagnetic record, to argue that Nuna assembled at about the same longitude as the latest supercontinent Pangaea (320–170Ma), whereas Rodinia formed through introversion assembly over the legacy Nuna subduction girdle either ca. 90° to the west (our slightly preferred model) or to the east before the migrated subduction girdle surrounding it generated its own degree-2 mantle structure by ca. 780 Ma. Our interpretation is broadly consistent with the global LIP record. Using TPW and LIP observations and geodynamic model predictions, we further argue that the Phanerozoic supercontinent Pangaea assembled through extroversion on a legacy Rodinia subduction girdle with a geographic centre at around 0°E longitude before the formation of its own degree-2 mantle structure by ca. 250Ma, the legacy of which is still present in present-day mantle.